Peran Artificial Intelligence Untuk Mendeteksi Fraud Dalam Audit: Sebuah Studi Literatur - Suci Nurlayli Alimatu Sholiqah; Retno Ayu Widyastuti; Tri Ratnawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Artificial Intelligence (AI) is an intelligence that can independently find solutions to problems. AI in the audit process has positive aspects, such as improving inspection quality and saving time, on the other side it also threatens the sustainability of the auditing profession. This research uses literature studies. Data was obtained through previous research and literature studies, including in-depth analysis of existing literature. This research will include searching and evaluating literature sources that cover AI methods, algorithms, and applications in detecting fraud in audits, as well as identifying the advantages, disadvantages, and challenges related to the use of this technology. AI can help improve efficiency and effectiveness in the field of auditing. AI can assist auditors in document assessment, reduce auditor usage time, and detect fraud in company financial reports. However, AI cannot completely replace the role of auditors because there are processes that require human judgment. The role of auditors remains important in avoiding fraud detection errors and providing objective opinions.